Wellbeing – fashion or necessity? The importance of programs supporting employee well-being in human capital management - Małgorzata Sidor-Rządkowska; Mirosław Wójcik (Journal of Modern Science)
Objectives The aim of the article is to analyze the phenomenon of increasing popularity of well-being programs in organizations observed in recent years. This increase is so large that the question arises whether it is not a manifestation of the so-called fashion in management discussed in the introduction to the presented article.